2000
DOI: 10.1002/1521-4184(200012)333:12<397::aid-ardp397>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Does [meso-1,2-bis(2,6-dichloro-4-hydroxyphenyl)ethylenediamine]-dichloroplatinum (II) Act on the Hormone-Sensitive, Murine Breast Cancer as a Biological Response Modifier? Part II. Studies on the Influence of [meso-1,2-bis(2,6-dichloro-4-hydroxyphenyl)ethylenediamine]dichloroplatinum(II) on the Specific Immune Defense in MXT-M-3,2 Breast Cancer Bearing Mice

Abstract: The anti‐tumor activity of [meso‐1,2‐bis(2,6‐dichloro‐4‐hydroxyphenyl) ethylenediamine]dichloroplatinum(II) on the MXT‐M‐3,2 breast cancer implanted into B6D2F1 mice was not significantly reduced by splenectomy or co‐administration of cyclosporine A. Neither did the use of T‐lymphocyte‐deficient NMRI (nu/nu) mice as hosts substantially influence its anti‐tumor effect. Obviously, [meso‐1,2‐bis(2,6‐dichloro‐4‐hydroxyphenyl)ethylenediamine] dichloroplatinum(II) does not act by an enhancement of the specific immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Rather a mechanism that involves also other cells of the host e.g. such of the immune system must be taken into consideration. , This hypothesis is supported by the investigations of Curran et al Their data suggest that ERβ or possibly a novel receptor are involved in mediating estrogen action on natural killer cell activity. This could raise the potential for therapeutic modulation with selective estrogen receptor modulators.…”
Section: Discussionmentioning
confidence: 94%
“…Rather a mechanism that involves also other cells of the host e.g. such of the immune system must be taken into consideration. , This hypothesis is supported by the investigations of Curran et al Their data suggest that ERβ or possibly a novel receptor are involved in mediating estrogen action on natural killer cell activity. This could raise the potential for therapeutic modulation with selective estrogen receptor modulators.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the mammary tumor-inhibiting effects cannot be caused by the antagonism of tumor growth stimulating endogenous estrogens. Rather a mode of action must be taken into consideration described by Schlemmer et al [25][26][27][28] They proposed an indirect mode of action for an estrogenic active platinum complex due to its hormonal properties, which involves other cells of the host as well, e.g., cells of the immune system. This is supported by the results on the MCF-7 cell line.…”
Section: Resultsmentioning
confidence: 99%
“…However, a complex mode of action including cytotoxic potency and estrogenlike effects, the latter probably giving rise to an improvement of anti-breast cancer activity, has been excluded. Estrogenlike effects would be (a) hindrance of the cellular processing of Pt-modified DNA by overexpression of high mobility group domain proteins 5 and (b) interruption of the vicious circle of mutual growth stimulation of breast cancer cells and granulocytes/ macrophages by reducing the formation of key cytokines [8][9][10][11] (see Introduction). In the test on the MCF-7-2a cell line, the cytotoxic threo-2-PtCl 2 did not stimulate luciferase expression as an indication for estrogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…ovariectomized mouse bearing ER + MXT-M-3,2 breast cancer) mainly by its estrogenic potency; its low cytotoxicity played a subordinate role. Studies on the mode of action showed that meso -6-PtCl 2 triggered an ER-mediated signal in breast cancer cells, which interrupted the tumor growth stimulation by cells of the phagocytic system and restored the natural immune defense, leading to tumor regression. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation